1985
DOI: 10.1093/oxfordjournals.aje.a114013
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Dementia of the Alzheimer Type

Abstract: A case-control study to assess factors of possible etiologic significance to dementia of the Alzheimer type was conducted with 78 male cases diagnosed in 1979-1982 at the Veterans Administration Medical Center in Minneapolis, Minnesota and age-race-sex-matched hospital and neighborhood controls (14 of 16 autopsied cases were histopathologically confirmed). Information was obtained on variables relevant to vital, genetic, and immunologic hypotheses, and on possible occupational and environmental exposures, drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(98 citation statements)
references
References 0 publications
4
92
0
2
Order By: Relevance
“…Methods of exposure determination in these studies vary, ranging from proxy reports [22][23][24] to self-administered mail-in questionnaires 25 to structured in-person interviews. 2,24 Determination of the level of occupational pesticide exposure is particularly difficult because it depends on the duration of use, the method of application, and whether safety equipment was used, or used properly.…”
Section: 21-25mentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of exposure determination in these studies vary, ranging from proxy reports [22][23][24] to self-administered mail-in questionnaires 25 to structured in-person interviews. 2,24 Determination of the level of occupational pesticide exposure is particularly difficult because it depends on the duration of use, the method of application, and whether safety equipment was used, or used properly.…”
Section: 21-25mentioning
confidence: 99%
“…Results of investigations into the reliability of data collection methods used in the Agricultural Health Study 27 suggest that our methods may be more accurate than those applied in studies that use mail back questionnaires 25 and reports from proxy informants which were necessarily used in case-control studies. [22][23][24] The Agricultural Health Study analysis showed that structured questionnaires with cues yield better information than open-ended questioning. 27 Farmers' self-reported pesticide use has shown good reliability 27,29 regardless of the age or education level of participants.…”
Section: 21-25mentioning
confidence: 99%
“…We excluded reviews, editorials, nonhuman studies, and case reports; we also excluded publications that explored the association between serum pesticide levels and risk of AD, as these data could not be meta-analysed because of their different formats in the reporting of results. After excluding those studies that failed to meet the inclusion criteria, a total of seven publications were selected, providing data on three cohort 12,17,18 and four case-control studies [19][20][21][22] . The flowchart of literature selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…169 The moderate consumption of alcoholic beverages, however, has been associated with comparatively better cognitive function in two studies: The Zutphen Elderly Study 170 and the Honolulu Asia Aging Study. 171 A third study, The Rotterdam Study, demonstrated that moderate alcohol consumption reduced the risk of vascular dementia in particular, and also that of Alzheimer's disease in individuals aged 55 years or older, 172 which is supported by the results of other studies by Huangand colleagues 173 and Mukamal and colleagues.…”
Section: Effect Of Wine On Alzheimer's Disease and Dementiamentioning
confidence: 99%